Development of a United Antarctic Research Data information environment - Globa, L.; Kuzyn, I.; Moroz, I.; Mochalkina, K.; Novogrudskaya, R. (Ukrainian Antarctic Journal, 2012)
The article deals with the approach for the designing of the National Antarctic Data Center knowledge Internet-portal. The process of portal knowledge representation model designing is discussed. The portal ontology model and all its components formal description is given.